Cultures of war Pearl Harbor, Hiroshima, 9-11, Iraq - Dower, John W (W.W. Norton New Press, 2010)
A groundbreaking comparative study of the dynamics and pathologies of war in modern times. Over recent decades, Pulitzer-winning historian John W. Dower has addressed the roots and consequences of war from multiple perspectives. Here he examines the cultures of war revealed by four powerful events--Pearl Harbor, Hiroshima, 9-11, and the invasion of Iraq in the name of a war on terror. The list of issues examined and themes explored is wide-ranging: failures of intelligence and imagination, wars of choice and "strategic imbecilities," faith-based secular thinking as well as more overtly holy wars, the targeting of noncombatants, and the almost irresistible logic--and allure--of mass destruction. Dower also sets the U.S. occupations of Japan and Iraq side by side in strikingly original ways. He offers comparative insights into individual and institutional behavior and pathologies that transcend "cultures" in the more traditional sense, and that ultimately go beyond war-making alone.--From publisher description.